Triangle and quadrilateral learning design through GeoGebra assisted discovery learning - Dinda Nur Salsabila; Dedi Muhtadi; Eko Yulianto (Beta: Jurnal Tadris Matematika, 2024)
[English]: This research aims to design and implement a triangle and quadrilateral learning design using the discovery learning model supported by GeoGebra, as well as evaluating students' learning outcomes. The research method employed design research consisting of three stages: preliminary design, design experiment, and retrospective analysis. Data collection in this study involved the use of observation techniques to observe relevant aspects during the learning process. In addition, the learning process was recorded to gather data on student activities during the design experiment phase. Interviews were used to delve deeper into information regarding potential issues found. This research was conducted in the secondary school SMP Negeri 2 Cisaga, involving two classes, namely the pilot experiment class and the teaching experiment class. The research results indicated that incorporating tile and gypsum profile contexts into teaching the concepts of perimeter and area of triangles and quadrilaterals significantly contributes to help students developing a fundamental understanding of the related concepts and formulas. Furthermore, the utilization of learning trajectory within the context of tiles and gypsum profiles through the discovery learning model with the assistance of GeoGebra positively influences students' comprehension of the perimeter and area of triangles and quadrilaterals. [Bahasa]: Penelitian ini bertujuan untuk merancang dan menerapkan desain pembelajaran segitiga dan segi empat menggunakan model pembelajaran penemuan yang didukung oleh GeoGebra, serta mengevaluasi hasil belajar siswa. Metode yang digunakan adalah penelitian desain (design research) yang terdiri dari tiga tahap: desain awal, eksperimen desain, dan analisis retrospektif. Pengumpulan data dalam penelitian ini melibatkan penggunaan teknik observasi untuk mengamati aspek-aspek relevan selama proses pembelajaran. Selain itu, proses pembelajaran direkam untuk mengumpulkan data mengenai aktivitas siswa selama fase eksperimen desain. Wawancara digunakan untuk menggali lebih dalam informasi mengenai potensi masalah yang ditemukan. Penelitian ini dilakukan di SMP Negeri 2 Cisaga, melibatkan dua kelas, yaitu kelas eksperimen pilot dan kelas eksperimen pengajaran. Hasil penelitian menunjukkan bahwa penggabungan konteks ubin dan profil gypsum dalam pengajaran konsep keliling dan luas segitiga serta segi empat secara signifikan berkontribusi dalam membantu siswa mengembangkan pemahaman dasar mengenai konsep dan rumus terkait. Selanjutnya, pemanfaatan jalur pembelajaran dalam konteks ubin dan profil gypsum melalui model pembelajaran penemuan dengan bantuan GeoGebra secara positif mempengaruhi pemahaman siswa terhadap keliling dan luas segitiga dan segi empat.